A Mechanism for Improving the Spectral Efficiency in mu-MIMO for 5G and Beyond Networks - Eirini Barri; Christos Bouras; Vasileios Kokkinos; Aspasia Koukouvela (The 19th International Symposium on Mobility Management and Wireless Access (ACM Mobiwac 2021), November 22 – 26, 2021, Alicante, Spain, 2021)
The ultimate challenge that arises in 6G and 5G and beyond networks is how the mobile networks of the future will be able to cope with the constantly increasing number of devices. In Multiuser Multiple-Input and Multiple-Output (mu-MIMO), the base station basically serves many users at the same time using the same frequency. The topic considered in this paper is the spectral performance in Downlink mu-MIMO. This paper’s goal is to improve the achieved spectral efficiency of the communication system, as well as the achieved reliability of the communication link. An algorithm based on downlink scheduling and the resource allocation is proposed to achieve maximum spectral use of the system. Considering user’s demands, this paper’s mechanism is able to allocate the potential user of the queue to the ”best antenna” based on its demands and distance. That provokes a larger number of devices that can be supported, always according to the specifications stated in IEEE 802.11ax.